Professionalization of bibliometric research assessment. Insights from the history of the Leiden Centre for Science and Technology Studies (CWTS). (14th December 2017) - Petersohn, Sabrina; Heinze, Thomas
Abstract: In recent years, the use of quantitative metrics in research evaluation has grown considerably. This article recasts the emergence of evaluative bibliometrics as an academic research field and quantitative research assessment as a field of professional experts in the Netherlands by focusing on one expert organization that has shaped both: the Centre for Science and Technology Studies (CWTS) at the University of Leiden. Based on Abbott's theory of professions and drawing on a comprehensive data set, including both archival and interview data, we show that the new professional field has been fostered by political actors in the Dutch science policy arena and that expertise was predominantly institutionalized in CWTS as a leading research institute and a provider of bibliometric research assessment services. Since the 2010s, CWTS has been challenged by ready-made bibliometric solutions provided by large database providers and publishing houses that increasingly attract non-experts to perform bibliometric assessments.